2021
DOI: 10.1186/s12889-021-12368-2
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of health inequalities depending on educational level using nationally representative survey data in Japan, 2019

Abstract: Background In recent years, socioeconomic differences in health statuses and behaviors have not been investigated from the nationally representative survey data in Japan. In this study, we showed differences in representative health behaviors and statuses depending on educational level using a nationally representative survey data in Japan. Methods Aggregated (not individual level) data from the Comprehensive Survey of Living Conditions in 2019 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In addition to education being associated with HL (Furuya et al, 2015; Verney et al, 2019), lower education was associated with multiple chronic diseases (Johnson‐Lawrence et al, 2017; Pathirana & Jackson, 2018), limitations in physical functioning due to disease (Zajacova & Montez, 2017), and has been identified as a barrier to health. Less educated individuals might have difficulty in obtaining effective information about health issues, which might affect healthy living and self‐care (Okui, 2021). Moreover, the results indicated that education was significantly associated with online health information searching, consistent with previous studies revealing that the more educated participants were, the more they searched for health information online (Medero et al, 2022; Weber et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to education being associated with HL (Furuya et al, 2015; Verney et al, 2019), lower education was associated with multiple chronic diseases (Johnson‐Lawrence et al, 2017; Pathirana & Jackson, 2018), limitations in physical functioning due to disease (Zajacova & Montez, 2017), and has been identified as a barrier to health. Less educated individuals might have difficulty in obtaining effective information about health issues, which might affect healthy living and self‐care (Okui, 2021). Moreover, the results indicated that education was significantly associated with online health information searching, consistent with previous studies revealing that the more educated participants were, the more they searched for health information online (Medero et al, 2022; Weber et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4 Among these factors, education level and health literacy play a pivotal role. 2,[5][6][7][8] Lower education levels of the patient and/or the primary caregiver have been associated with prolonged disease duration, poor follow-up and retention rates, and increased diseaserelated morbidity. 1 Surgical interventions for spinal pathologies are particularly susceptible to being impacted by poor patient educational levels and poor health literacy due to the inherent complexity of these pathologies.…”
Section: Methodsmentioning
confidence: 99%
“…These social determinants of health are composed of a multitude of factors, including sex, race, socioeconomic status (SES), employment status, and housing status 4 . Among these factors, education level and health literacy play a pivotal role 2,5–8 . Lower education levels of the patient and/or the primary caregiver have been associated with prolonged disease duration, poor follow-up and retention rates, and increased disease-related morbidity 1 .…”
mentioning
confidence: 99%
“…Public surveys of general companies have identi ed the time and nancial problems as reasons for CCS hesitancy. Many existing reports are questionnaire-based descriptive reports [6,7]. However, few have included the social backgrounds of those who did not take the test [8].…”
Section: Introductionmentioning
confidence: 99%
“…Public surveys of general companies have identi ed the time and nancial problems as reasons for CCS hesitancy. Many existing reports are questionnaire-based descriptive reports [6,7]. However, few have included the social backgrounds of those who did not take the test [8].In Japan, the impact of coronavirus disease (COVID-19) is signi cant, with the rst declaration of a state of emergency issued in March 2020, followed by "stay-at home restrictions" for approximately two and half years until the fourth declaration was lifted in September 2022 [9].Regarding cancer screening and the withholding of medical examinations due to the COVID-19 disaster, the U.S. National Cancer Institute reported in 2020 that the COVID-19 pandemic affected the cancer screening uptake rate [10].…”
mentioning
confidence: 99%